Acculturation of Malay Culture in the Mantenan Tradition of Javanese Ethnic Anthropolinguistic Approach - Sofiani; Rozanna Mulyani; Alemina Br Perangin-angin (PT FORMOSA CENDEKIA GLOBAL, 2022)
The research study aims to describe the performance of text, context and context as well as find meaning and function, values and norms, and BM local wisdom in the acculturation of BM Mantenan EJ: Anthropolinguistic Approach. The research method used is descriptive qualitative with an ethnographic approach to know, experience and understand in depth a cultural event in society. The research data is speech data or lingual text obtained from informants through observation, interviews, documentation, audio and video recordings. expressive speech acts, the context contains proxemics, gestures, materials, traditional clothing and halls. The context is the context of the situation, social context, cultural context and ideological context. The content of BM acculturation in EJ's Mantenan Anthropolinguistic approach is an expression of gratitude and blessing for the bride and groom so that they are always given safety, happiness, success and kept away from all difficulties. The function of culture found is as a form of entertainment, a tool for supporting cultural institutions and as a medium for character education. Acculturated values in Mantenan EJ Anthropolinguistic Approach are religious values, logical values, ethical and aesthetic values. mark. The norms found are norms of decency, norms of customary law. The local wisdom is togetherness and cooperation in community life, kinship, mutual respect, gratitude, cultural preservation and harmony